A New Perspective of Learning Arabic in Lombok as A World Halal Tourism Destination - Dony Handriawan (Arabic Education Program IAIN Pekalongan, 2020)
This article analyzes the importance of re-orientation in achieving the goals of Arabic Teaching and Learning (ATL). The process is adapted to the local context and the needs of the place where the Arabic language is taught. Lombok currently becomes the main halal tourism destination as a consequence of the awards in the tourism sector achieved by Lombok in 2015 and 2016. In 2015 Lombok won two prestigious awards as